EVALUASI KINERJA DINAS KESEHATAN KOTA SEMARANG DALAM RANGKA PENGENDALIAN PENYAKIT DEMAM BERDARAH DENGUE ( DBD ) DI LINGKUNGAN KOTA SEMARANG PERIODE TAHUN 2011 - Wicaksono, Arif (Journal of Politic and Government Studies, 2013)
Concerning to emerge The Good Governance, bureaucrate performance has the mainrole, especially solving every problems popped out among civic social life, consideringfunction of state institution has the role to accomodate the needs of its people. Mostfrequently problems could be varied from different aspects, such as health, education,economy, demography, transportation, etc. Those problems will be an responsibility for all ofstate institution in the process to reach the development of welfare in every aspect.The health quality of Semarang citizens has tied by some key factors such as healthservices, spreading disease, number of citizens with illness, healthness environment, deathcase caused by illness, health facilities, and human resources among service providers, thestakeholders, until the civilians. This research is about enforce the evaluation of bureaucrateperformance, especially The Health City Department of Semarang in the task of respondingevery health problems among citizens, one of it is the policy for cope with the most dangerousdisease which become the biggest problems of Semarang city at this time, the DengueHaemorragic Fever (DHF). The source purposively chosen is from the Head Section of P2B2(Animal-sourced disease precautionary), with DHF Coordinator Staff, Head Officer ofNgaliyan Public Health Centre, and the member of The Family Welfare Development inNgaliyan region.The results of this research shows that performance ofÂ The Health City Department ofSemarang in cope with DHF problems in 2011 already showed the rise if compared by theresults in 2010. Beside the positive, some problems and obstruction still appear, frequentlycome from human resources performance quality. So that, the policy to cope with DHFproblems by The Health City Department of Semarang has to be regained, particularly in thehuman resources aspect.Keywords: Performances, Problems and obstructions, DHF Precautionary.